A qualitative evaluation of integration in a community health centre - M.R. de Villiers; K. Sandison (South African Family Practice)
Integration of primary health care services is taking place as part of the development of a District Health System. This study was undertaken to determine factors influencing the integration process and to assess the extent to which interventions facilitating the integration of health care personnel in a primary health care centre had been effective. The focus of the study was on the staffs experiences of the change process and its impact on them and the service delivered, therefore the use of a qualitative method. The results indicated four key areas that had been affected by the intervention, namely: infrastructure and systems; patient care; community participation; and staff interaction. Changes in the external environment and external facilitation of the process were positive contributors. Factors acting as restraining forces were service conditions discrepancies, fear and resistance to change, continuation of existing management structures, and cultural differences between the organisations. The main findings this study highlighted are that it is critical to deal with the individual fears of people about the perceived and real losses that the change will precipitate. It is important to have external facilitation as it brings a measure of objectivity. Lastly, change needs to happen on multiple levels and behaviour change is made significantly more difficult if it is not supported by changes to conditions and structures as well.